Convenience as care: Culinary antinomies in practice. (September 2017) - Meah, Angela; Jackson, Peter
This paper addresses the social and cultural significance of convenience food, often regarded as among the least healthy and most unsustainable of dietary options, subject to frequent moral disapprobation. The paper focuses, in particular, on the relationship between convenience and care, conventionally seen in oppositional terms as a culinary antinomy. Informed by a 'theories of practice' approach, the paper presents empirical evidence from ethnographically-informed research on everyday consumption practices in the UK to demonstrate how convenience foods can be used as an expression of care rather than as its antithesis. The paper uses Fisher and Tronto's theorisation of caring about, taking care of, caregiving and care-receiving to draw out the dynamics of this morally contested social practice.